Book review: Ashvin Immanuel Devasundaram, India's New Independent Cinema: The Rise of the Hybrid. (June 2019) - Chatterjee, Tupur
Ashvin Immanuel Devasundaram, India's New Independent Cinema: The Rise of the Hybrid . New York, NY: Routledge, 2016, 292 pp., ISBN: 978-1-138-18462-6.